The Improved of Counselor Competencies through Scientific Article Writing Training Using Digital Citation Application - Daharnis Daharnis; Zadrian Ardi; Ifdil Ifdil (Jurnal Konseling dan Pendidikan, 2018)
The track record of the development of science will be easily traced by the scientific community through various forms of scientific information. Social workers have thousands and even millions of aspects and scope of scholarship that can be used as materials to develop science. As a professional, social workers including counselors, psychologists and other professions are urgently needed to develop their insights and knowledge about human and territorial behavior that can be addressed through counseling services. Various things will certainly be realized by the research or research and publish through scientific articles. However, in reality, BK / Konselor teachers have not been too concerned and develop the ability and competence in the field of scientific articles. Various cases and services that should be used as material for scientific and professional discussions are not published in the form of scientific articles so that in general the parameters of the development of BK services in schools can not be known with certainty. These conditions require BK teachers to be able to have competence and skills in writing scientific articles and using digital citation program / software.